The archaeology of Roman Portugal in its western Mediterranean context - Stek, Tesse Dieder; Carneiro, André, 1973- (Oxbow Books, 2022)
"The Archaeology of Roman Portugal contributes to the wider debate on Roman imperialism and expansionism, by bringing to the fore a much-underrepresented area of the Roman empire, at least in English-language scholarship: its westernmost edge in modern day Portugal. Highlighting the perspective from Roman Portugal contributes to our understanding of the Roman empire, through presenting both an extraordinary landscape in the sense of economic opportunities (ocean resources, marble and metal mining), and also settlement history. The volume presents new data and insights from both archaeology and ancient history, discussing their significance for our understanding of Roman expansion and imperialism. A key goal of the volume is to discuss how the Portuguese panorama compares to other areas of the Iberian peninsula, and to better integrate Portuguese scholarship in the academic debate on the Mediterranean Roman world, and to contextualise it firmly within the wider Iberian and Western Mediterranean. The volume brings together an internationally diverse team of scholars in archaeology and ancient history from Portugal, Spain, Germany, the UK, the US, the Netherlands, Belgium and Italy. It explicitly discusses different national and disciplinary research traditions and historical frameworks in order to assess the potential of integrating best practices in archaeological approaches and methodology"--